2019
DOI: 10.18203/2394-6040.ijcmph20192329
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and problems of menstruation among the adolescent school girls of Delhi: a cross-sectional study

Abstract: Background: Adolescence is the period of rapid physical growth, psychological and social changes. This period is marked by the onset of menarche in the girls. Menstruation is a natural biological process experienced by all adolescent girls and women in reproductive age. The menstrual cycle is characterized by variability in volume, pattern and regularity. Conversely, variability in menstrual cycle characteristics and menstrual disorders are common among adolescent girls. The objectives of the study were to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…It was higher than the age of menarche reported in other studies. 9,11,12,14,17,18 Majority (69.4%) of the girls reported regular periods and 26.4% of the girls reported irregular periods, this was similar to the results reported in other studies. 9,11,12,17 The mean length of the menstrual cycle reported in this study was 26.28 ± 3.25 days and mode is 28 days which was similar to the once reported in other studies (9).…”
Section: Discussionsupporting
confidence: 90%
“…It was higher than the age of menarche reported in other studies. 9,11,12,14,17,18 Majority (69.4%) of the girls reported regular periods and 26.4% of the girls reported irregular periods, this was similar to the results reported in other studies. 9,11,12,17 The mean length of the menstrual cycle reported in this study was 26.28 ± 3.25 days and mode is 28 days which was similar to the once reported in other studies (9).…”
Section: Discussionsupporting
confidence: 90%
“…Another matter of concern was the poor supply of IFA and deworming tablets in schools as reported by the study participants. In line with these findings, Singh and coworkers found that only 2.8% of school (government) going girls (n= 210) consumed IFA in the previous year to their survey and only 3.8% had consumed deworming tablet in last six months (38) . This could be attributed to ineffective implementation of the AMB programme.…”
Section: Journalscambridgeorg/jnsmentioning
confidence: 76%
“…With regards to anaemia prevention, only two female interviewees talked about cooking food in iron vessels, and five girls mentioned consumption of iron-rich dietary sources and IFA tablets in preventing and treating anaemia. Some of these preventive measures were reported by school girls in a crosssectional study conducted in New Delhi, India (38) . Disappointingly, these practices were not implemented by the girls in the Delhi-based study (38) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity has started by promoting Nutritional Action in Schools with 3 intervention packages, namely providing weekly TTD for young women, physical activity, and consuming balanced nutritious food (5). The target for anemia screening activities includes 100 percent of adolescent girls in 12 priority provinces for editing and 80 percent of adolescent girls in 24 other provinces.…”
Section: Introductionmentioning
confidence: 99%